O formador de professores no curso de licenciatura em Matemática do Instituto Federal de Alagoas: da profissionalização à prática pedagógica - Brasileiro, Regina Maria de Oliveira (2019)
This research focuses on training of teachers and relationship between theory and practice developed during formative process of teacher trainers. He was part of Academic Cooperation Program (Procad - CNPq - 2012-2017), articulated between State University of Rio de Janeiro, Federal University of Rio Grande do Norte and Federal University of Alagoas, in Continuing Education axis. The objective of this study was to understand how professors of undergraduate courses in mathematics perceive themselves as teachers, considering their pedagogical practice, their professionalization and their qualification as potential or not in training of mathematics teachers. The pedagogical practices developed in degree course in Mathematics of Federal Institute of Alagoas (Ifal) constitute in formative spaces for the teacher-training teachers, allow or not the articulation of practical theory in the formation of the future teachers? In order to respond to the problematization, a qualitative research was chosen (LÜDKE; ANDRÉ, 2008), with a focus on the case study (YAZAN, 2016). The interview and observation techniques and the documentary analysis were used for the construction of the corpus, also using the technique of content analysis (BARDIN, 2008) based on date analys though semantic categorization. Mathematics professors of Federal Institute of Alagoas (Ifal), who work in Câmpus Maceió in Degree in Mathematics, were constituted as practicing subjects of study. This work is based on Lima and Silva (2011), Hargreaves (1998), Marinho (2014), Gatti (2014), Tardif (2002), Imbérnon (2010), Silva (2006), Torres (2005), Fiorentini), among others. The results show that the teachers recognize the importance of the initial formation to the exercise of their teaching activity, at the same time as they attribuite the experience as mathematics teachers in the basic education essential for acting as teacher educators. They affirm that the pedagogical proposal of the degree course in mathematics of Ifal has a differential of its formative process, that makes possible the articulation of practical theory, however it is still a way to built daily. They realized that there is an overloading/intensification of their work, lacking time to plan their pedagogical practices, reinforcing perspective of professional isolation and individualism of the teaching culture, a fact that has implied in their pedagogical practices and reinforcing the qualification as a strong contribution to training of teachers. It is concluded that Ifal presents itself as an institution with potential for the offer of undergraduate courses, in which the teachers of the degree course in mathematics assume the role of teacher trainers, being able to contribute with the training of future teacher in what refers the theoretical-practical relationship. However, constraints inherent in the dimensions of organizational culture of Ifal and professional teaching culture still make it difficult to establish practices that articulate practical theory between basic education and the formation of future teacher.